PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBANTUAN MEDIA POTRET BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS - Muzzilawati, Serli; Aeni, Ani Nur; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2017)
Based on early research conducted in students class IV SDN Sindang I about matter diversity nations and local culture. The study students not based expected, because in a learning still centered on teacher and media learning used less attractive so students most still passive. Hence, diterapkanlah a model learning cooperative type investigation. Media potraits cultures to improve learning learning outcomes students. Methods used is research the act of a class. Preliminary data study results students or researchers with 27% students are declared be completed while 73% expressed has not been solved, on the much as 54% expressed had been completed while 46% expressed have not been solved, on theÂ 89% of those who did not had been completed while 11% expressed have not been dolved, and in the many 100% of those who did not had been completed. Based it the application of learning model cooperative type group investigation berbantuan media potrait culture have improve learning outcomes students.